Two types of additional absorption spectra in CaF2 crystals - Vorobyev А. А. Alexander Akimovich; Zavadovskaya E. K.; Lisitsyna L. A.; Lisitsyn V. M. Viktor Mikhailovich (1969, 1969)
В фонде НТБ ТПУ отсутствует